Christianity in tropical Africa : studies presented and discussed at the seventh International African Seminar, University of Ghana, April 1965 - Baëta, C. G.; Forde, Daryll, 1902-1973 (African ethnographic studies of the 20th century, 2018)
Originally published in 1968 this volume discusses the issues and problems relevant to Christianity in Tropical Africa. It includes historical studies of the earlier Catholic and Protestant missions and their relationship with African communities, traders and colonial administrations; the social and psychological aspects of conversion and responses to the teaching of the gospel and the impact of Christian teaching on indigenous beliefs; the analysis of modern trends such as separatism